A rare systemic etiology of heart failure and liver dysfunction. Issue 7 (3rd June 2019) - Lee, Christopher; Chau, Edward; Patel, Sumit; Zhao, Diana; Yang, Alexander H.; Lee, Brian T.; Alexander, Jacob; Ostrzega, Enrique; Sarte, Patrick
Abstract: Systemic amyloidosis is a rare condition that can manifest with cardiomyopathy, hepatic dysfunction, and renal disease. Diagnosis is often missed and/or delayed due to chronic multi‐system involvement and indeterminate signs and symptoms. Treatment generally involves systemic therapy and autologous stem‐cell transplantation. Abstract : Systemic amyloidosis is a rare condition that can manifest with cardiomyopathy, hepatic dysfunction, and renal disease. Diagnosis is often missed and/or delayed due to chronic multi‐system involvement and indeterminate signs and symptoms. Treatment generally involves systemic therapy and autologous stem‐cell transplantation.